HAES-LX-5% INFUSION-INDUCED STRUCTURAL CHANGES OF RATS’ RENAL CORTEX IN LATE PERIOD OF SKIN BURN INJURY - Лахтадир, Т.В. (World of Medicine and Biology, 2017)
The article presents and analyzes the results of the experimental investigation of structural changes of rat’s renal cortex in late period of skin burn injury under the conditions of the infusion by HAES-LX-5%. Infusion of HAES-LX-5% cause the clearly expressed nephroprotective effects. Thus, the of renal cortex is characterized by the presence of morphological changes in components of glomerular and tubular apparatus. To positive, on the essence, it is necessary to take structural presence of functional potential of podocytes due to safety of foot processes and stabilizing of thickness of basale membrane. Mitoptosis play a main role in the adaptation of the number and quality of mitochondria in tubular epithelial cells to new microenvironmental conditions in situation of burn disease. Massive mitoptosis leading to autophagy can result in cell death.